Diploid chromosome-level genome assembly and annotation for Lycorma delicatula - Anthony A. Snead; Fang Meng; Nicolas Largotta; Kristin M. Winchell; Brenna A. Levine (Scientific Data)
Abstract The spotted lanternfly (Lycorma delicatula) is a planthopper species (Hemiptera: Fulgoridae) native to China but invasive in South Korea, Japan, and the United States where it is a significant threat to agriculture. Genomic resources are critical to both management of this species and understanding the genomic characteristics of successful invaders. We report an annotated, haplotype-phased, chromosome-level genome assembly for the spotted lanternfly using PacBio long-read sequencing, Hi-C technology, and RNA-seq. The 2.2 Gbp genome comprises 13 chromosomes, and whole genome resequencing of eighty-two adults indicated chromosome four as the sex chromosome and a corresponding XO sex-determination system. We identified over 12,000 protein-coding genes and performed functional annotation, facilitating the identification of candidate genes that may hold importance for spotted lanternfly control. The assemblies and annotations were highly complete with over 96% of BUSCO genes complete regardless of the database (i.e., Eukaryota, Arthropoda, Insecta). This reference-quality genome will serve as an important resource for development and optimization of management practices for the spotted lanternfly and invasive species genomics as a whole.